The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.25115/ejrep.v16i46.2232
|View full text |Cite
|
Sign up to set email alerts
|

Atención e impulsividad en Niños con Alta Capacidad Intelectual y Niños con TDAH

Abstract: Introducción. Comportamientos asociados a la alta capacidad intelectual, como la inatención y respuesta anticipada amenudo se confunden con el trastorno por déficit de atención e hiperactividad (TDAH) y dificultan su identificación. El objetivo del presenta trabajo fue analizar el desempeño de los alumnos con alta capacidad intelectual y alumnos con TDAH en la atención sostenida y la impulsividad.Método. Participaron un total de 25 niños con alta capacidad intelectual, edad promedio 6.15 años y 25 niños con TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Our results were expected because they reaffirm that teacher experience had a positive relationship with their knowledge about gifted students. These findings were similar to others reported in the literature [45][46][47] that suggested that experienced teachers recognise higher self-efficacy for inquiry in gifted students and employ diverse instructional practices with students with special learning needs [48][49][50][51][52][53][54]. Lastly, studies suggested that an important predictor of teachers' knowledge about gifted students is based on contact with gifted students, since they help teachers recognize their characteristics and educational needs [41,51].…”
Section: Teacher Teaching Experience and Training Effects On Teacher ...supporting
confidence: 86%
See 2 more Smart Citations
“…Our results were expected because they reaffirm that teacher experience had a positive relationship with their knowledge about gifted students. These findings were similar to others reported in the literature [45][46][47] that suggested that experienced teachers recognise higher self-efficacy for inquiry in gifted students and employ diverse instructional practices with students with special learning needs [48][49][50][51][52][53][54]. Lastly, studies suggested that an important predictor of teachers' knowledge about gifted students is based on contact with gifted students, since they help teachers recognize their characteristics and educational needs [41,51].…”
Section: Teacher Teaching Experience and Training Effects On Teacher ...supporting
confidence: 86%
“…In Mexico, there are limited studies about teacher knowledge concerning gifted education [53][54][55]. These studies can be grouped into two main areas: gifted characteristics and educational strategies.…”
Section: Factors Affecting Teacher Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Tras analizar los datos y resultados anteriores llegamos a una serie de conclusiones compartidas con otros casos similares (Valadez, 2018;Serrano et al, 2019;Gómez-León, 2020b; Rusca y Cortez, 2020):…”
Section: Conclusiones Y Discusiónunclassified
“…A pesar de estas reglas estandarizadas a la hora de proceder al diagnóstico, son numerosos los autores (Pérez, 2014;Valadez et al, 2018;Álvarez-Cárdenas, 2019;Semelas, 2019) que opinan que muchos niños son mal calificados como personas con TDAH; así, Álos y Ruiz (2013, p.13) comentan que:…”
Section: Introductionunclassified